In silico Exploration of Potent Phytoecdysteroids Targeting Multiple Receptors in Non-Small Cell Lung Cancer - Adhikari, Bishnu; Phuyal, Ashish; Phunyal, Anuraj; Upadhyaya, Nabin; Waiba, Amar; Adhikari, Achyut (Journal of Nepal Chemical Society, 2025)
Cancer is a genetic disease that disrupts the normal functioning of cells. This is a disease wherein there is the survival of the old cells that should die while the growth of new and not-needed cells takes place. In this regard, the study has explored virtual screening, molecular docking, and server-based approaches - 10 ns RMSF calculations and prediction of inhibition towards cancer to identify probable candidates from the database of Phytoecdysteroids. Brainesteroside A showed better binding affinities at -9.1 kcal/mol as compared to the reference drug, Gefitinib (-7.0 kcal/mol), and native ligand (-8.5 kcal/mol), for the 7VKO receptor. For the 3ZBF receptor, Ecdysterone22-benzoate 25-O-β-D-glycoside showed better binding affinities, - 9.4 kcal /mol, as compared to the reference drug Gefitinib (-7.0 kcal/mol) and native ligand (-8.4 kcal/mol). Similar binding values with the 3VHK receptor were found in this study, with a better affinity of Polypodine B 2-β-D-glucoside, -9.3 kcal/mol, than either the reference drug (Gefitinib) with values of -7.0 kcal/mol, or native ligand, -9.1 kcal/mol binding values. This study resulted in the promising identification of ROS1, Trka, and VEGFR2 potential inhibitors that showed favorable pharmacokinetic, and pharmacodynamics properties with server-based results. Therefore, this study proposed the use of Phytoecdysteroids as a promising candidate for further lung cancer drug development.